Cytotoxic Effect of Betulinic Acid on Vascular Smooth Muscle Cells - Vadivelu, Raja Kumar (2009)
Betulinic Acid (BA) is a widely available plant-derived triterpene reported as a selective cytotoxic activity against cancer cell of neuroectodermal origin and leukaemias. Interestingly, this will be first report to demonstrate the cytotoxic effect of BA in VSMCs. First, MTT cytotoxic assay was used to measure cell viability of VSMCs with predetermined concentrations of BA for 24h, 48h and 72h. The results obtain indicated that BA inhibit the growth and proliferation of VSMCs in a dose dependent manner IC10 of 0.4μg/ml, IC25 of 1μg/ml and IC50 of 3.8 μg/ml significantly (P<0.05). Secondly, the genotoxic potential associated to exposure to BA was assessed on VSMCs in vitro by the comet assay. BA exhibits low level of DNA damage and not likely to increase the level of DNA damage after 24 h exposure. Moreover, Flow cytometric analysis revealed that BA treatment FOR 24 h induced cell cycle arrest at the G1 phase and caused the appearance of a sub-G1 DNA peak at 48 h. Finally, the cell death morphology indicates that the percentage of apoptotic at 24 h were 12.43 ± 1.55% and at 48 h were 23.17 ± 1.73%, the percentage of necrotic cells at 48 h were 14.63 ± 1.45%. An increase percentage of apoptotic cells at 72 h were 45.92 ± 1.45%. In conclusion, exposure of BA to VSMCs initiate early DNA damage, arrest at G1 phase and induce apoptosis.